Papel da glicose na inativação de Candida albicans na terapia fotodinâmica antimicrobiana - Silva, Tamires de Oliveira (2020)
Candida albicans, in the presence of glucose, can increase the amount of intracellular photosensitizer and the amount of cell inactivation in resistant strains. However, as this fungus evolved with the same catabolic repression pathways as its ancestor, S. cerevisiae, this inherited characteristic contributes to the suppression of glucose uptake when glucose is abundant. Therefore, the objective of this work is to evaluate the role of different glucose concentrations in the antimicrobial behavior of photodynamic therapy in Candida albicans. For a better understanding of the photodynamic processes, the study was developed with Candida albicans strains ATCC10231, YEM14 (wild) and YEM 15 (resistant). (1) microbiological tests were carried out to investigate cell inactivation, (2) uptake to verify the uptake of photosensitizer and measurement of reactive oxygen species to check for degradation. The strains were submitted to treatment without glucose, with 1mM and 20mM of glucose associated with 100uM methylene blue. For irradiation, an LED (Light emitted diode) equipment developed at UNINOVE by Prof. Dr. Alessandro Deana of the Biophotonics Program Applied to Health Sciences. The equipment emits central light at 660 nm and was adjusted to produce radiant power of 473 mW and the samples were irradiated at 1, 3 and 6 minutes. In the microbiological assay, the concentration of 1mM was the most efficient in cell inactivation for all strains. Regarding the photosensitizer incorporation capacity, all strains showed a better incorporation result with 1mM of glucose. Regarding the formation of reactive oxygen species, the presence of glucose did not cause degradation or affect the formation of species. We can conclude that higher concentrations of glucose can activate the repression genes but an appropriate minimum concentration can favor aPDT in C.albicans even in resistant strains.